Australia's shifting global engagement: the stuttering rise of financial services and city-based competitiveness. Issue 3 (3rd July 2018) - O'Neill, Phillip; Knight, Eric; Wójcik, Dariusz
ABSTRACT: A key theme of Global Restructuring (R. H. Fagan and M. Webber. 1994. Global Restructuring: The Australian Experience . Melbourne: Oxford University Press) is the dramatic rise of financial capital flows into and out of Australia commencing with the financial deregulation measures of the early 1980s. The book's concern is with the impacts of this deregulation on the materials sectors of the Australian economy, chiefly on the food, manufacturing and minerals sectors. In the book's back story, the Australian banks emerge as institutions able to appropriate value from the overall package of changes. This paper looks at aspects of the Australian financial sector 20 years on from the Fagan and Webber analysis. Reflecting on data collected after 1994 the paper outlines key changes in the industry mix within the Australian economy and, in particular, the rise of financial and business services. In so doing it assesses the shifts in the financial and business services sector that have occurred since the time of Global Restructuring and presents an analysis of these shifts in the context of the rise of international financial services centres, especially in the Asian region. Based on these findings and assessments, the paper proposes a research agenda for scholars interested in the competitiveness of Australian firms, especially in the context of opportunities for financial services growth within the wider region.